Handbook of research on contemporary storytelling methods across new media and disciplines - Mihaes, Lorena Clara, 1975-; Andreescu, Raluca; Dimitriu, Anda, 1986- (Information Science Reference, 2021)
"This book provides the relevant theoretical framework which concerns storytelling in modern society, as well as the newest and most varied analyses and case studies in the field, offering radical forms of storytelling in traditional disciplines and methods of telling stories across newer media, which are seldom the object of academic inquiry"--